Reflexo dos pilares institucionais nas práticas esg: um estudo de caso na universidade federal da integração Latino- Americana - Martins, Jessica Damian Luiz (2025)
This research aims to understand how ESG practices occur within the environment of a Federal University, using Institutional Theory and Scott’s (1995, 2001) Institutional Pillars as the analytical framework. Methodologically, it is a case study, which enables in-depth analysis, and is characterized as a qualitative and exploratory research, based on content analysis of UNILA’s 2023 Integrated Management Report, as well as interviews with university staff. The study is justified by the need to understand how a federal university internalizes and implements ESG practices, considering its specificities as a public institution. The analysis of the Integrated Report highlighted social inclusion, transparency, and diversity. The social dimension was the most prominent, evidenced by affirmative policies and student assistance programs. In the governance dimension, transparency stood out through the Integrity Program and internal audits. In the environmental dimension, challenges were observed in expanding sustainable initiatives, with actions such as waste management and energy efficiency. The interviews indicated the predominance of the Regulatory Pillar, followed by the Normative Pillar and, lastly, the Cultural-Cognitive Pillar. ESG practices are strongly influenced by external regulations and normative requirements. The Normative Pillar was expressed in the alignment with national and international standards, such as the SDGs. The Cultural-Cognitive Pillar, although less prevalent, reflected the institution’s commitment to inclusion and diversity. The research showed that ESG practices at UNILA go beyond merely responding to external demands, reflecting internal institutional dynamics that shape their adoption and consolidation. The findings expand understanding of how institutional factors influence organizational sustainability, highlighting the role of Institutional Pillars in shaping governance, social responsibility, and sustainability practices. One of the most significant insights was the identification of the Regulatory Pillar as the main driver of ESG practices at the university. The consolidation of these practices requires greater balance between regulatory pressures, institutional norms, and cultural change, fostering more integrated internalization of ESG principles in public higher education. The results contribute to advancing the literature on ESG in the public sector, offering support for the development of more effective and sustainable institutional policies in Brazilian federal universities.